2012
DOI: 10.1016/j.jelekin.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between history and physical examination factors and change in lumbar multifidus muscle thickness after spinal manipulation in patients with low back pain

Abstract: Understanding the clinical characteristics of patients with low back pain (LBP) who display improved lumbar multifidus (LM) muscle function after spinal manipulative therapy (SMT) may provide insight into a potentially synergistic interaction between SMT and exercise. Therefore, the purpose of this study was to identify the baseline historical and physical examination factors associated with increased contracted LM muscle thickness one week after SMT. Eighty-one participants with LBP underwent a baseline physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…In addition, it should also be noted that we have obtained a significant correlation between multifidus failure and back pain. a finding which is in accord with previous studies which have linked low back pain with possible atrophy of the multifidus muscle [11][12][13][14][15], a finding which we have also been able to confirm (in women) in the present study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, it should also be noted that we have obtained a significant correlation between multifidus failure and back pain. a finding which is in accord with previous studies which have linked low back pain with possible atrophy of the multifidus muscle [11][12][13][14][15], a finding which we have also been able to confirm (in women) in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, various authors have linked lumbar pain to possible multifidus atrophy [11][12][13][14][15]. Given this link, it is unsurprising that multifidus alterations can be predictive of different spinal injuries [9].…”
Section: Introductionmentioning
confidence: 99%
“…41 Furthermore, another study indicated that none of the variables comprising the stabilization CPR was associated with increased activation of the lumbar multifidus following spinal manipulation. 43 Finally, any changes in activation of the lumbar multifidus that were observed immediately after manipulation did not seem to be consistently sustained 3 to 4 days after the application of the technique. 42 Therefore, we do not believe the manipulation techniques in our study were likely to produce long-lasting or clinically significant changes in recruitment of the spinal musculature of our patients.…”
Section: Discussionmentioning
confidence: 87%
“…Elles ne sont pas encore clairement établies et nous pouvons retrouver, chez les mêmes auteurs, des analyses multivariées aux résultats différents avec des facteurs pronostics différents : lors de l'étude précédente, les lombalgiques devaient satisfaire peu ou prou aux critères énoncés précédem-ment par Childs [15] et repris depuis dans la littérature comme permettant une réussite franche du traitement par manipulation vertébrale (lombalgie de moins de 16 jours, pas de douleur au delà du genou, pas de kinésiophobie ou catastrophisme marqué, au moins un segment vertébral apparaissant hypomobile à la mobilisation passive postéro-antérieure, au moins une rotation médiale de hanche supérieure à 358) ; une deuxième étude des mêmes auteurs [16] a tenté d'analyser plus finement les facteurs susceptibles d'influencer favorablement le résultat : quatre variables apparaissent prédictives de l'augmentation de section du multifide à l'aide de la manipulation vertébrale : souffrir depuis moins de trois mois, ne pas avoir de douleur en L5 lors d'un appui dorso-ventral sur l'épi-neuse, présenter une douleur à l'élévation active jambe tendue du membre inférieur (active straight leg rising), avec des symptômes qui se centralisent préférentiel-lement lors des extensions lombales répétées ; Il s'avère donc que seul le caractère aigu de la lombalgie soit la variable commune la plus fortement associée à l'augmentation de surface du multifide grâce à la manipulation vertébrale. une troisième étude [17] a retrouvé comme variables associées étroitement avec les atrophies du multifide un âge inférieur à 40 ans, la présence de mouvements anormaux (comme le fait de se relever en s'appuyant sur ses cuisses), une élévation du membre inférieur supérieure à 908, la présence d'une hypermobilité lombale, un prone instability test positif.…”
Section: Règles De Prédiction Clinique Et Atrophie Du Multifideunclassified